Effectiveness of Proprioceptive Neuromuscular Facilitation Stretching Along with Foam Roller On Shoulder Girdle Muscles Tightness in Truck Drivers - Pawar, Chetana Anand; Kadam, Namrata Anil (Journal of Neonatal Surgery, 2025)
Bckground : Flexibility is an important aspect of proper human function. The shoulder girdle muscles are required for many daily activities including bathing, driving, combing, lifting weights, and controlling shoulder mobility. Muscle tightness develops when the joint's capacity and range of motion are reduced. Tension in the shoulder girdle muscles is a leading cause of injury. Objective : The study sought to investigate the efficacy of PNF stretching in conjunction with a foam roller on shoulder girdle muscular tension in truck drivers, as well as which method was preferable to get the best outcomes and provide the most advantages to the participants. Methods : This randomized clinical trial will assess the impact of an intervention on shoulder girdle muscles tightness in truck drivers. Thirty participants with truck drivers, will be selected via random sampling. Inclusion criteria include the participants aged 27 to 50 years, active working minimum 15 to 20 years experience, No significant musculoskeletal injuries or chronic conditions that may interfere with the study . Exclusions include history of shoulder or back injuries in past 6 months, use of medications that affect muscle strength. The outcomes are wall angel test , upper trapezius and levator scapulae stretch test, scapular assistance test and ROM pre and post treatment. Participants will undergo a six-week intervention, with data analyzed post-assessment. Ethical approval and informed consent will be obtained. Result : Based on the statistical analysis, the effectiveness of PNF stretching along with foam roller on shoulder girdle muscles tightness in truck drivers shows highly significant.(p<0.0001). Conclusion : The study concluded that the use of foam roller with PNF stretching evidenced a significantly greater improvement in reducing shoulder girdle muscles tightness in truck drivers